Chinese legalism and Islamic views of justice: a comparison based on the political thought of Han Fei and Ibn Khaldun - Wu, Jinke; Russli Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study addresses the lack of comparative research examining the political dimensions of justice as conceived by Han Fei, representing Legalist thought in ancient China, and Ibn Khaldun, a prominent Islamic scholar. The objective is to elucidate how these two realist thinkers, each writing in a period of political fragmentation, conceptualize justice within their respective frameworks. Methodologically, the research employs a comparative philosophy approach, centring on textual analysis of Han Feizi and Al-Muqaddimah, alongside secondary sources on Legalist and Islamic political traditions. The findings reveal that both Han Fei and Ibn Khaldun view the nature of humanity with scepticism and emphasize the necessity of strong governance to ensure social order. However, their interpretations of law diverge: Han Fei portrays it as an impersonal instrument designed to enforce compliance under a ruler’s absolute power, whereas Ibn Khaldun integrates law with divine authority, thereby constraining secular power through religious principles. An important implication of this contrast is that both frameworks can, under certain conditions, legitimize authoritarian rule: in Legalist thought, through an unwavering focus on the ruler’s will, and in Islamic contexts, when religious law is manipulated to serve despotic ends. Understanding these convergences and divergences deepens our appreciation of how different cultural and historical settings shape the pursuit—and the potential pitfalls—of achieving justice.